Therapeutic Efficacy of Nasoenteric Tube Feeding in Children Needing Enteral Nutrition - Chen, Mi-Chi; Chao, Hsun-Chin; Yeh, Pai-Jui; Lai, Ming-Wei; Chen, Chien-Chang (Frontiers in Pediatrics, 2021)
Background: There is limited information on therapeutic benefits and tube-related complications of pediatric nasoenteric (NE) tube feeding. We viewed, from different clinical aspects, NE tube feeding in children who are under intolerable conditions. Methods: A 10-years retrospective study enrolled 77 pediatric patients who underwent an endoscopic-guided placement of the NE tube for enteral nutrition. The evaluated data, including growth parameters, feeding volume, parenteral nutrition (PN) dependence, and nutritional markers [serum hemoglobin (Hb) and albumin] before and after NE tube feeding were compared. Tube-related complications and major adverse events were also recorded. Results: A total of 77 patients (including 50 males) underwent 176 endoscopic-guided placements of the NE tube with an average duration of 133.7 (6.0–1,847.3) days. The gastroesophageal reflux disease-related symptoms (vomiting, desaturations, and aspiration pneumonia) improved in 71.4% of patients. Feeding volume increased significantly after intervention, especially in patients with delayed gastric emptying, from 144.8 ± 28.5 to 1,103.1 ± 524.7 ml/days (p < 0.001). Weaning from PN was successfully achieved in 84.3% of patients with an average of 9.33 ± 7.30 days. About 16 patients (20.8%) were subsequently highly compatible with oral feeding after NE tube placement for an average of 24.7 ± 14.1 days. Patients either without neurologic dysfunction or with no ventilator-dependent status had a higher chance of shifting to oral feeding. Weight-for-age z-scores increased by 0.15 ± 1.33 after NE tube intervention. One NE tube-related adverse event, which caused bowel perforation at 6 days post-insertion, was recorded. No direct tube-related mortality was observed. Conclusions: Endoscopic-guided NE tube placement is a relatively safe, non-invasive procedure for pediatric patients who require enteral nutrition. Feeding via NE tube showed beneficial effects such as improvement in symptoms, PN weaning, and maintenance of body growth without major tube-related complications.